MRI correlates of neuropsychiatric symptom progression in pre‐dementia GRN and C9orf72 mutation carriers. (31st December 2021) - Lee, Hyunwoo; Chatterjee, Atri; Popuri, Karteek; Beg, Mirza Faisal; Mackenzie, Ian R; Wittenberg, Dana; Rademakers, Rosa; Hsiung, Ging‐Yuek Robin
Abstract: Background: Frontotemporal dementia (FTD) patients with mutations in the C9orf72 or the GRN genes frequently exhibit neuropsychiatric symptoms (NPS), which may precede the onset of dementia. We hypothesized that the burden and progression of NPS in pre‐dementia mutation carriers are associated with structural abnormalities detectable in brain MRI. Method: We analyzed data from 42 participants before onset of dementia (11 C9orf72+ mutation carriers, 8 GRN+ mutation carriers, and 23 non‐carrier family members (NCs); mean±SD age: 46y±11, 50y±9, and 53y±8 respectively) recruited through the University of British Columbia FTD Study. Participants were assessed longitudinally for NPS with Neuropsychiatric Inventory (NPI), Frontal Behavioural Inventory (FBI) and Iowa Scale of Personality Change (ISPC) (mean follow‐up: 8.4y). Participants also underwent 1.5T MRI at the first and third annual visits (mean interval: 28±8m). If a participant developed FTD during the follow‐up (N=2), we only analyzed observations collected before the conversion. We processed T1‐weighted MRI to calculate annualized volumetric changes in the grey‐matter, the white‐matter and the hypointense white‐matter signal‐abnormalities (WMSA), within the entire brain and lobar region‐of‐interests. We applied a random‐slope model to the NPI, FBI and ISPC scores to estimate subject‐specific slopes of their progression. Then, we applied a linear model to evaluate the association between the estimated slopes and the MRI measures, among the genetic groups. Covariates included sex, age, baseline assessment scores, baseline WMSA and total white‐matter volumes. Result: There were non‐significant baseline group differences in the MRI or NPS measures. Overall, a higher rate of frontal lobar WMSA accumulation was associated with a higher rate of NPI score increase. However, GRN+ carriers had a faster progression of NPS compared to NCs, and the higher NPI slope was associated with a higher rate of frontal lobar white‐matter volume loss. The FBI and ISPC slopes were not significantly associated with the MRI measures. Conclusion: Prior to the onset of FTD, the emergence of NPS in mutation carriers may be correlated with the degree of frontal lobar white‐matter lesions. In GRN+ carriers, the progression of NPS, as represented by NPI score increases, may also be associated with frontal white‐matter volume loss.